2015
DOI: 10.18276/cej.2015.3-02
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gender and Recurrent Low Back Pain on Lifting Style

Abstract: Abstract. Objective: The purpose of this study was to examine the influence of gender and existing, recurrent low back pain (rLBP) on lower extremity and trunk mechanics, as well as neuromuscular control, during a lift task. Design: A multivariate design was used to examine the effects of gender and group on biomechanical and neuromuscular control variables in randomized symmetric and asymmetric lifting. Methods: 68 Males and females with rLBP and healthy performed symmetric and asymmetric weighted box lifting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Recurrent LBP patients have diminished trunk 49 and lower extremity strength, flexibility, and range of motion, 22 , 39 , 50 as well as altered neuromuscular control. 22 , 39 , 51 These patients presented with reduced activity in the EO and GM and increased activity in Mf in both initial and final position of lifting in comparison to healthy control. Laird et al 49 reviewed 43 studies on the lumbopelvic kinematics in LBP patients and found that these patients have reduced lumbar range of motion, move more slowly, and have reduced proprioception compared with people without LBP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recurrent LBP patients have diminished trunk 49 and lower extremity strength, flexibility, and range of motion, 22 , 39 , 50 as well as altered neuromuscular control. 22 , 39 , 51 These patients presented with reduced activity in the EO and GM and increased activity in Mf in both initial and final position of lifting in comparison to healthy control. Laird et al 49 reviewed 43 studies on the lumbopelvic kinematics in LBP patients and found that these patients have reduced lumbar range of motion, move more slowly, and have reduced proprioception compared with people without LBP.…”
Section: Discussionmentioning
confidence: 99%
“…Lifting technique was based on the discretion of the individual and the subject’s box weight was determined by their maximum psychophysically acceptable weight ( Table 1 ). 21 , 22 Participants performed 3 weighted box (0.65 m long, 0.35 m wide, and 0.15 m high) lifting trials with VPAC and 3 trials without VPAC to a 1 m high table in right side directions ( Figures 1 and 2 ). The VPAC condition was presented in random order.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Di Stasi, Myer, Hewett, 2013;Griffin, Agel, Albohm, 2000) Additional evidence suggests that when the knee is flexed less than 40° represents the most unprotected range for ACL tears as consistently reported in cadaveric (Kanamori, Woo, Ma, 2000;Markolf, O'Neil, Jackson, 2004), in vivo (Heijne, Fleming, Renstrom, 2004;Pedowitz, O'Connor, Akeson, 2003) and computer simulation (Pandy, Shelburne, 1997;Pflum, Shelburne, & Torry, 2004) studies of ACL strain or force. Biomechanical analyses seek to improve understanding of the mechanisms of knee injury and to find ways to reduce knee injury incidence (Di Stasi et al, 2013;Haddas, James, Hooper, 2015;Haddas, Yang, Sizer, 2015;Jung et al, 2013;Liu-Barba, Hull, Howell, 2007;Patzkowski et al, 2012). These biomechanical studies usually include analysis of knee joint deformation, where joint architecture immutably constrains and guides movement outcomes (Liu-Barba et al, 2007;Wilson, Feikes, Zavatsky, O'Connor, 2000).…”
Section: Introductionmentioning
confidence: 99%